A Rare Form of Major Self-mutilation in a Patient with Delusional Disorder - Shahbaz Habib Faridi; Mohammad Amir Usmani; Bushra Siddiqui; Mohammad Aslam (Wolters Kluwer Medknow Publications, 2016)
Self-mutilation is defined as the intentional, direct injuring of body tissue without suicidal intent. In this article we report the case of a 45-year-old male who presented to the emergency department with a history of incising his abdomen and chopping his intestines into pieces. The patient also brought the chopped pieces along with himself. He was operated on, and a resection and anastomosis was done. Postoperative recovery of the patient was uneventful. After a psychiatric assessment was done, it was found that he was suffering from delusional disorder. Owing to such rare presentation of major self-mutilation in a patient with delusional disorder, this case is being reported here.